Gla-rich protein (GRP) as an early and novel marker of vascular calcification and kidney dysfunction in diabetic patients with CKD: a pilot cross-sectional study - Silva, Ana P. (2020)
Vascular calcification (VC) is one of the strongest predictors of cardiovascular risk in chronic kidney disease (CKD) patients. New diagnostic/prognostic tools are required for early detection of VC allowing interventional strategies. Gla-rich protein (GRP) is a cardiovascular calcification inhibitor, whose clinical utility is here highlighted. The present study explores, for the first time, correlations between levels of GRP in serum with CKD developmental stage, mineral metabolism markers, VC and pulse pressure (PP), in a cohort of 80 diabetic patients with mild to moderate CKD (stages 2-4). Spearman's correlation analysis revealed a positive association of GRP serum levels with estimated glomerular filtration rate (eGFR) and α-Klotho, while a negative correlation with phosphate (P), fibroblast growth factor 23 (FGF-23), vascular calcification score (VCS), PP, calcium (x) phosphate (CaxP) and interleukin 6 (IL-6). Serum GRP levels were found to progressively decrease from stage 2 to stage 4 CKD. Multivariate analysis identified low levels of eGFR and GRP, and high levels of FGF-23 associated with both the VCS and PP. These results indicate an association between GRP, renal dysfunction and CKD-mineral and bone disorder. The relationship between low levels of GRP and vascular calcifications suggests a future, potential utility for GRP as an early marker of vascular damage in CKD.